APPLICATION OF BROMELAIN LITTER SOLID COMPOST INDUCED BY LIGNINOLITIK Trichoderma sp. FUNGUS TOWARDS NUMBER OF LEAVES AND CHLOROPHYL CONTENT CHILI PLANTS (Capsicum annuum L.) - Jihan Haura; Bambang Irawan; Salman Farisi; Yulianty Yulianty (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Piles of uncontrolled pineapple peel waste have a negative impact that will affect various aspects of life, either directly or indirectly. Therefore, pineapple peel waste that can no longer be processed can be used for making compost. The taste of pineapple can be degraded biologically with the help of enzymes that can be produced by microorganisms. One of the microorganisms that can support the decomposition process is a group of fungi. In this study, the fungus Trichoderma sp. (Bioggp 5) is a ligninolytic fungus. Trichoderma sp. is a saprophytic soil microorganism that attacks natural pathogenic fungi and is beneficial to plants. The purpose of this study was to determine the effect of solid bromelain compost inoculum of ligninolytic fungi (Trichoderma sp.) on leaf number and chlorophyll content of chili plants (Capsicum annum L.) and the best dose of compost that could be used. This study used a completely randomized design (CRD) with 7 treatments, namely T0 (control), T1 (1.4% pure bromelain), T2 (1.7% pure bromelain), T3 (2% pure bromelain), T4 (1, 4% bromelain + leaf litter), T5 (1.7% bromelain + leaf litter), T6 (2% bromelain + leaf litter). The parameters used were the number of leaves and chlorophyll content. And the results obtained from this study were the T3 dose (2% pure bromelain) was the best dose for the number of leaves, while the T2 dose (1.7% pure bromelain) was the best dose for chlorophyll content.